2022
DOI: 10.3389/fendo.2022.955687
|View full text |Cite
|
Sign up to set email alerts
|

Targeting-intratumoral-lactic-acidosis transcatheter-arterial-chemoembolization for non-islet cell tumor hypoglycemia secondary to a liver metastatic solitary fibrous tumor: A case report and literature review

Abstract: Doege–Potter syndrome is a rare paraneoplastic syndrome characterized by non-islet cell tumor hypoglycemia secondary to a solitary fibrous tumor. Doege–Potter syndrome always presents with recurrent fasting hypoglycemia, which can occasionally be life-threatening. The best choice of treatment for Doege–Potter syndrome and solitary fibrous tumor is complete resection. However, when it is unfeasible, local-regional treatment can be used as a palliative therapy. Herein, we report a case of a 46-year-old man with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Sunitinib, another tyrosine kinase inhibitor was used to treat 31 patients and reportedly achieved 6% RECIST PR and 52% SD (12). Recently, a case report described the benefit of targeting intratumoral lactic acidosis TACE for non-islet cell tumor hypoglycemia secondary to hepatic metastasis of SFT (13). Therefore, improved chemotherapeutic agents and endovascular therapies, such as TACE, may have a synergistic effect, and further studies are needed to elucidate their precise role.…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib, another tyrosine kinase inhibitor was used to treat 31 patients and reportedly achieved 6% RECIST PR and 52% SD (12). Recently, a case report described the benefit of targeting intratumoral lactic acidosis TACE for non-islet cell tumor hypoglycemia secondary to hepatic metastasis of SFT (13). Therefore, improved chemotherapeutic agents and endovascular therapies, such as TACE, may have a synergistic effect, and further studies are needed to elucidate their precise role.…”
Section: Discussionmentioning
confidence: 99%
“…Complete resection or tumor debulking of the Big‐IGF‐II producing SFT is the most promising treatment for patients with DPS, particularly in light of the fact that the majority of metabolic alterations due to increased Big‐IGF‐II are fully reversible 10,12,17 . Adjuvant chemotherapy and radiotherapy might also improve the general outcome 18,19 . Apart from surgery, glucocorticoids may be considered for long‐term therapy, as they appear to suppress secretion of Big‐IGF‐II and may contribute a protective effect for hypoglycemia by increasing insulin resistance 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 12 , 17 Adjuvant chemotherapy and radiotherapy might also improve the general outcome. 18 , 19 Apart from surgery, glucocorticoids may be considered for long‐term therapy, as they appear to suppress secretion of Big‐IGF‐II and may contribute a protective effect for hypoglycemia by increasing insulin resistance. 3 Despite variable expression of somatostatin receptors (SSTR) in SFT, Octreotide has so far been reported to be ineffective in treatment of DPS.…”
Section: Introductionmentioning
confidence: 99%
“…The objective response rate (ORR) was 100% when sodium bicarbonate was employed, while the rate was 44.4% with conventional TACE in a nonrandomized cohort, and 63.6% in a randomized study ( 14 ). A recent case study reported that a 46-year-old man with Doege-Potter syndrome, secondary to liver and pancreatic metastatic solitary fibrous tumors, achieved clinical cure of hypoglycemia and well-controlled liver metastatic tumor after receiving six rounds of TILA-TACE treatment ( 15 ). These findings suggest that sodium bicarbonate solution may have potential therapeutic benefits for cancer treatment, although further studies are needed to confirm these results.…”
Section: Introductionmentioning
confidence: 99%